THEORY DEVELOPMENT: PATIENT’S LIFE CAPACITY THEORY THROUGH SELF- EMPOWERMENT MODEL IN CARDIAC REHABILITATION - Widodo, Gipta Galih; Irawati, Dewi; Hamid, Achir Yani S.; Siswanto, Bambang Budi; Purwaningsih, Puji (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2023)
Introduction: Cardiac rehabilitation can provide extensive benefits and prevent recurrent heart disease, however participation in cardiac rehabilitation rates is still low. Health promotion strategies witheducation can improve the ability and independence to carry out cardiac rehabilitation at home. The purpose of this study is to describe, explore, predict, and control phenomena to create a theoretical construction of a self-empowerment model in cardiac rehabilitation programs at home.Methods: Theory construction uses procedures that include establishing the central concept, establishing the source of the theory, determining the meaning of the theory, identifying concepts, examining concept definitions, identifying statements, establishing relationships between concepts, analyzing the logical adequacy of the theory, determining the usefulness of the theory, and explaining the level of generalizability and parsimony of the theory.Results: The self-empowerment model can be used to provide nursing care to patients with cardiac rehabilitation, especially cardiac rehabilitation at home. This model can optimize the achievement of patient capacity by increasing patient ability and independence. Patients are responsible, confident, and disciplined to change their behavior toward optimal health.Conclusions: This model is specific to the cardiac rehabilitation environment (home-based cardiac rehabilitation) to increase the participation of patients after cardiovascular interventions in cardiacrehabilitation programs to improve patient capacity which includes physical health, functional capacity,and quality of life.